PENGARUH MODAL INTELEKUAL TERHADAPPROFITABILITAS, PRODUKTIVITAS, NILAIPASAR PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 – 2017 - Inda Gumilang; Lona noviani (LPPM Universitas Banten jaya, 2022)
This study aims to examine the effect of intellectual capital and on profitability, productivity, market value and growth listed on the Indonesia Stock Exchange in 2014-2017. By using the Public Value Added Intellectual Capital (VAIC) model, the study examines the relationship between the efficiency of Value Added Intellectual Capital (VAIC) from the three main sources of Value Added Human Capital (VAHU), Sructural Capital Value Added (SCVA). Profitability is measured using Return On Assets (ROA), Productivity is measured using Asset Turn Over (ATO), Market Value is measured using Price to Book Value (PBV) and Growth is measured using Earning Growth (EG). The research sample used a purposive sampling method. The research design is complex, secondary data types, data sources are obtained from www.idx.co.id, the websites of each Banking and Investment Gallery Indonesia Stock Exchange Untirta Serang. The data analysis technique uses Statistical Package The Social (SPSS). The test results prove that probabilities affect intellectual capital, productivity affects intellectual capital, market value influences intellectual capital and growth influences intellectual capital